KESANTUNAN BERBAHASA GURU DAN SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS IX SMP NEGERI 2 GALESONG - Suci Multazam Suri; Usman Usman; Sakaria Sakaria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the form of language politeness in interactions between teachers and students, and students and teachers. This study used descriptive qualitative method. The source of this research data is the result of interaction between students and teachers. The results of this study indicate that the form of politeness from teacher to student interaction obeys 5 forms of maxims namely, the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of modesty, and the maxim of sympathy. While the form of politeness from student to teacher interactions obeys 5 forms of maxims, namely, the maxim of wisdom, the maxim of generosity, the maxim of agreement, the maxim of modesty, and the maxim of sympathy.